Knowledge and attitudes of family health strategy professionals regarding the bone marrow transplant network - Borges, Ana Maria Machado; Adami, Fernando; Alves, Beatriz da Costa Aguiar; Azzalis, Ligia Ajaime; Junqueira, Virginia Berlanga Campos; Fonseca, Fernando Luiz Affonso (International Journal Of Community Medicine And Public Health, 2018)
Background: The bone marrow transplant (BMT) network includes factors from the moment donors sign up to the performance of the transplantation itself in specialized units. The current study aims to analyze the knowledge and attitudes of health professionals regarding this network. Methods: This is a quantitative, exploratory, descriptive study with 63 participants. Data were collected by means of questionnaires that included questions on the profile of the professionals and the bone marrow transplant network. Results: Professionals know what the national registry of bone marrow donors (REDOME) is (60.3%) and where registration can be done (68.3%). However, they were not registered as bone marrow donors (71.4%) and they did not know how to locate where patients’ records were stored (77.8%) or the units where BMTs are performed (60.3%). Conclusions: It is of utmost importance to stimulate the knowledge of professionals, particularly on those aspects related to recipients and transplant units.